2016
DOI: 10.1590/1678-457x.05016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bioactive compounds, antioxidant activity and minerals in landraces of pumpkin (Cucurbita moschata) cultivated in Southern Brazil

Abstract: The objective of this work was to evaluate the genetic variability for the synthesis of bioactive compounds and minerals in pumpkin (Cucurbita moschata) landraces. Total phenolic compounds, carotenoids, antioxidant activity and minerals were evaluated in 10 accessions of Cucurbita moschata landraces from the Genebank of Embrapa Temperate Agriculture (Pelotas -RS, Brazil). Twenty plants of each accession were cultivated in the field during the spring/summer of 2013/2014. After harvesting of mature fruits, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 21 publications
1
24
3
5
Order By: Relevance
“…O Banco Ativo de Germoplasma (BAG) de Cucurbitáceas, da Embrapa Clima Temperado, conserva 640 acessos de diferentes espécies cultivadas dos gêneros Citrullus, Cucumis, Cucurbita, Lagenaria, Luffa, Momordica e Sicana, sendo que 85 acessos são variedades crioulas de Cucurbita maxima. Porém, apenas uma pequena parte do acervo total do BAG já foi caracterizada (Neitzke et al, 2009;Priori, 2011;Priori, 2015;Fischer, 2012;Fischer et al, 2015;Fischer et al, 2016;Priori et al, 2012;Priori et al, 2013;Priori, et al, 2017). Para a realização deste trabalho, nove variedades crioulas de C. maxima foram selecionadas, seguindo-se alguns critérios, como a quantidade de sementes disponíveis no BAG e suficientes para a implantação do experimento, os dados de passaporte (como local de coleta, características dos frutos, reveladas pelos agricultores que doaram as sementes, como formato, cor da casca e tamanho dos frutos).…”
Section: Introductionunclassified
“…O Banco Ativo de Germoplasma (BAG) de Cucurbitáceas, da Embrapa Clima Temperado, conserva 640 acessos de diferentes espécies cultivadas dos gêneros Citrullus, Cucumis, Cucurbita, Lagenaria, Luffa, Momordica e Sicana, sendo que 85 acessos são variedades crioulas de Cucurbita maxima. Porém, apenas uma pequena parte do acervo total do BAG já foi caracterizada (Neitzke et al, 2009;Priori, 2011;Priori, 2015;Fischer, 2012;Fischer et al, 2015;Fischer et al, 2016;Priori et al, 2012;Priori et al, 2013;Priori, et al, 2017). Para a realização deste trabalho, nove variedades crioulas de C. maxima foram selecionadas, seguindo-se alguns critérios, como a quantidade de sementes disponíveis no BAG e suficientes para a implantação do experimento, os dados de passaporte (como local de coleta, características dos frutos, reveladas pelos agricultores que doaram as sementes, como formato, cor da casca e tamanho dos frutos).…”
Section: Introductionunclassified
“…Yellow pumpkin (Cucurbita moschata) is rich in carbohydrates and carotenoids that can function as an antioxidant (Kim et al, 2012). Several studies confirmed the antioxidant capacity of pumpkin, including those carried out by Gumolung et al (2013), Idayu (2017) and Priori et al (2017). PF has been used into different composite flours for fortification purpose, some of them with rice flour for baby biscuits making (Sundari, 2011), cornflour for cereal making (Ramadhani et al, 2012), and wheat flour for bread making (Lestario et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Priori et al [38] evaluated the genetic variability for the synthesis of bioactive compounds, total phenolic compounds, carotenoids, antioxidant activity, and minerals of 10 accesses of pumpkin (C. moschata) landraces. They found a high genetic variability for the synthesis of phenolic compounds, carotenoids, antioxidant activity, and minerals, with the most promising C52 and C389 accessions, due to their high levels of total carotenoids.…”
Section: Pumpkins (Cucurbita Moschata)mentioning
confidence: 99%